Rapid Detection of HIV-1 and 2 Antibodies by using Oral Fluid: A Multicentric Pilot Study in India - Nallan CSK Chaitanya; R Pinakapani; Pavan Kumar; Rajeshwari Annigeri; G Raghu Rao; A Amareswar; Veena Ramanna (Wolters Kluwer Medknow Publications, 2011)
Introduction- Detection of HIV antibodies is done by the standard blood tests. Rapid tests provide results in few minutes. The OraQuick rapid HIV12 antibody test using oral fluid has not been tried in resource-limited settings in India. The aim was to evaluate the efficacy of the OraQuick test kit using oral fluid for HIV antibody detection in patients attending the dental hospitals. Materials and methods: This multicentric pilot study was administered on 134 consenting subjects- Seventy subjects were randomly screened at Visakhapatnam and 64 at Davangere, by OraQuick test using oral fluid and other standard HIV screening tests. The subjects and the test administrators were enquired regarding the convenience of the oral fluid test and blood tests. The results were compared and conclusions were drawn. Results: Seventy subjects were positive with both oral fluid and blood tests. Sixty-four subjects were negative with both the tests demonstrating 100% sensitivity and specificity. The oral fluid test was well accepted by all patients and test administrators. Conclusion: Our study revealed that the OraQuick test using oral fluid was found to be highly accurate, noninvasive screening test which ran be easily used in dental hospitals